The Coral Reefs and Fishes of St. Brandon, Indian Ocean Archipelago: Implications for Sustainable Fisheries - Melanie Ricot; Sruti Jeetun; Shakeel Yavan Jogee; Deepeeka Kaullysing; Nawsheen Taleb-Hossenkhan; Maina Joseph Mbui; Beatriz Estela Casareto; Yoshimi Suzuki; Diah Permata Wijayanti; Ranjeet Bhagooli (Diversity)
Understanding the factors influencing the variability in the composition of fish assemblages is essential for bolstering the resilience of coral reef ecosystems, effective coral reef management and maintaining sustainable fisheries. The benthic composition and reef fish assemblages at eight sites at the poorly studied St. Brandon, also known as a bank fisheries area in the Indian Ocean, were assessed to discern distribution patterns, including differences between channel (Passe Grand Capitaine, Passe Ile Longue-Canal Coco and Passe La Cayane) and non-channel (Chaloupe, Anchor Points 1 and 2, Bain des Dames, Pearl Island) sites and fisheries sustainability. The benthic composition exhibited clusters, revealing the distinct separation of Chaloupe which predominantly featured sand (75.26%) interspersed with sporadic coral patches characterized by live and dead corals and rubble. The three channel sites composed a cluster. Coral species across eight families were identified, with significant variability (p < 0.05) observed in their benthic cover, particularly live coral cover (LCC). Fish density and diversity analyses unveiled 58 fish species from 12 families, with no statistically significant disparity in density among sites. Total fish biomass (TFB) and target fish biomass (TB) ranged from 138.02 ± 65.04 to 4110.16 ± 3048.70 kg/ha and from 28.31 ± 24.52 to 3851.27 ± 2753.18 kg/ha, respectively. TFB and TB differed significantly (p < 0.05) among sites irrespective of channel and non-channel sites, with Pearl Island recording the highest biomass. TFB and TB recorded at five out of the eight surveyed sites exceeded the mean biomass benchmark (B0) for the Western Indian Ocean, set at 1150.00 and 560.00 kg/ha for TFB and TB, respectively. Functional group analysis unveiled six discrete groups influencing TFB, with scrapers being the most dominant. This study presents the first report on fish biomass surveys in St. Brandon, highlighting a case for sustainable fisheries in the waters of the Republic of Mauritius.